Insertion or ziegler-natta polymerization of olefins: science and technology - Chikkali, S. H.; Patel, K.; Netalkar, S. (Metal-catalyzed polymerization: fundamentals to applications, 2017)
One of the most disruptive discoveries of twentieth century has been metal-catalyzed polymerization of ethylene to polyethylene by Prof. Karl Ziegler from the Max Plank Institut Fuer Kohlenforschung, Mulheim, Germany. This discovery marked the beginning of an era, which revolutionized the field of chemistry, in particular, the field of polymer chemistry in many aspects and saw an avalanche of patents and publications. Unlike typical academic discoveries, this invention did not stop at the academic labs, but led to the development of a large-scale process that produces about 180 million tons of polyolefins (annually) today. 1 But the very obvious question that comes to our mind is what prompted Prof. Ziegler to react ethylene with the two components (that we will discuss later in this chapter)? It was not an overnight realization, but instead, it was rational analysis of a serendipitous observation and systematic experimentation by Prof. Ziegler.